Evaluation of a Systems-Based Tobacco Cessation Program Using Bedside Volunteers. Issue 3 (21st November 2018) - Taylor, Denise S; Medaglio, Dominique; Jurkovitz, Claudine T; Patterson, Freda; Zhang, Zugui; Gbadebo, Adebayo; Bradley, Elisabeth; Wessells, Rose; Goldenberg, Edward
Abstract: Introduction: Hospitalization and post-discharge provide an opportune time for tobacco cessation. This study tested the feasibility, uptake, and cessation outcomes of a hospital-based tobacco cessation program, delivered by volunteers to the bedside with post-discharge referral to Quitline services. Patient characteristics associated with Quitline uptake and cessation were assessed. Methods: Between February and November 2016, trained hospital volunteers approached inpatient tobacco users on six pilot units. Volunteers shared a cessation brochure and used the ASK-ADVISE-CONNECT model to connect ready to quit patients to the Delaware Quitline via fax-referral. Volunteers administered a follow-up survey to all admitted tobacco users via telephone or email at 3-months post-discharge. Results: Of the 743 admitted tobacco users, 531 (72%) were visited by a volunteer, and 97% (531/547) of those approached, accepted the visit. Over one-third (201/531; 38%) were ready to quit and fax-referred to the Quitline, and 36% of those referred accepted Quitline services. At 3 months post-discharge, 37% (135/368) reported not using tobacco in the last 30 days; intent-to-treat cessation rate was 18% (135/743). In a multivariable regression model of Quitline fax-referral completion, receiving nicotine replacement therapy (NRT) during hospitalization was the strongest predictor (odds ratios [OR] = 1.97; 95% confidence interval [CI] = 1.34 to 2.90). In a model of 3-month cessation, receiving Quitline services (OR = 3.21, 95% CI = 1.35 to 7.68) and having coronary artery disease (OR = 2.28; 95% CI = 1.11 to 4.68) were associated with tobacco cessation, but a volunteer visit was not. Conclusions: An "opt-out" tobacco cessation service using trained volunteers is feasible for connecting patients to Quitline services. Implications: This study demonstrates the feasibility of a systems-based approach to link inpatients to evidence-based treatment for tobacco use. This model used trained bedside volunteers to connect inpatients to a state-funded Quitline after discharge that offers free cessation treatment of telephone coaching and cessation medications. Receiving NRT during hospitalization positively impacted Quitline referral, and engagement with Quitline resources was critical to tobacco abstinence post-discharge. Future work is needed to evaluate the cost-effectiveness and sustainability of this volunteer model.